Portable electronic power converter for neon lamps - Recto, King Harold A. (2004)
Neon lamps are considered to be one of the most effective methods of advertising due its eye appeal, high efficiency, flexibility, and very low maintenance cost. Conventional neon lamp operation requires the use of special neon transformers. Neon transformers have poor regulation and the power they can deliver is limited by their size. There are around a hundred turns of heavy wires in the primary while there are thousands of turns of smaller wire in the secondary. This causes the input voltage to step-up from a few hundred volts to thousands of volts. With advances in power electronics, it is now possible to replace the conventional neon transformer with an electronic power converter that is more efficient, less bulky, less costly, portable and has adjustable output root-mean-square by using a DC to AC Converter (with all the necessary control circuits), a small transformer and a Cockroft-Walton voltage multiplier.